Determining Diagnostic Thresholds for Acute Postoperative Periprosthetic Joint Infection. (2nd December 2020) - Sukhonthamarn, Kamolsak; Tan, Timothy L.; Xu, Chi; Kuo, Feng-Chih; Lee, Mel S.; Citak, Mustafa; Gehrke, Thorsten; Goswami, Karan; Parvizi, Javad
Abstract : Background: The diagnosis of periprosthetic joint infection (PJI) in the early postoperative period remains a challenge. Although studies have established that serum C-reactive protein (CRP) and synovial markers may be useful, recent studies have suggested that the current thresholds used may lack sensitivity. The purpose of this study was to examine the role of serum CRP, erythrocyte sedimentation rate (ESR), synovial fluid white blood-cell (WBC) count, and polymorphonuclear neutrophil (PMN) percentage in the diagnosis of acute postoperative PJI and to identify the optimal threshold. Methods: This multicenter study included patients who were investigated for possible PJI within 90 days of an index arthroplasty. This study included 197 patients from 4 institutions who underwent total joint arthroplasty from 2000 to 2017. Of these patients, 123 were confirmed to have PJI, and 74 were ruled out as not having PJI (non-infected group). Analyses of receiver operating characteristic (ROC) curves and the area under the curve were performed to determine the value of each test and optimal cutoff values. Results: The optimal cutoff value was 6, 130 cells/μL for synovial fluid WBC count (91% sensitivity and 83% specificity), 39.8 mg/L for serum CRP (91% sensitivity and 87% specificity), 39.5 mm/hr for ESR (76% sensitivity and 67% specificity), and 79.5% for PMN percentage (95% sensitivity and 59% specificity). Reducing the acute period from 90 days to 30 days or 45 days made little difference in most threshold values. However, the optimal cutoff for synovial fluid WBC count was almost twice as high (10, 170 cells/μL) when using a 30-day definition instead of a 90-day definition. Conclusions: The calculated cutoffs in our study were substantially lower than the thresholds used by the Musculoskeletal Infection Society. The calculated values of this study should be used, as previous cutoffs may be too high and lack sensitivity. In addition, it appears that the threshold values, at least for some of the tests, change as the duration since the index arthroplasty lengthens. A continuum of threshold values that is dependent on the number of days since the index arthroplasty may need to be used for the diagnosis of acute PJI. Level of Evidence: Diagnostic Level III . See Instructions for Authors for a complete description of levels of evidence.